Kampung Adat Pulo: Preserving the Harmony of Customs, Religion, and Traditional Sundanese Architecture - Fitriani, Reni; Febriyani Nur Ahyar, Sarah; Aisah, Iis; Badrussalam, Habib; Nurholis, Egi (JAMASAN: Jurnal Mahasiswa Pendidikan Sejarah, 2025)
Pulo traditional village is the embodiment of a unique combination of customs, history and architecture. The Kampung Adat Pulo has a mix of religions, starting with the community embracing Hinduism, Islam emerged with the arrival of Embah Dalem Arif Muhamad who stopped by after the defeat of the Dutch VOC and spread Islam. There are still strong customs that must be adhered to in the Kampung Adat Pulo, including not being allowed to add buildings, the traditional village can only be occupied by six houses of six heads of families from the lineage of Embah Dalem’s daughters, which until now cannot be violated. And there are many other customs that cannot be violated, such as not being able to keep four-legged animals, not being allowed to hit large musical instruments such as gongs and many more. The architecture of Kampung Adat Pulo buildings is valued as a characteristic of traditional Sundanese buildings that are based on nature. which is still preserved.